A Critical Analysis of Abū Rayyah's Perspectives on Ḥadīth Recording - Sanusi Lafiagi (Penerbit Hellow Pustaka, 2025)
Abū Rayyah, a prominent 20th-century Egyptian Islamic scholar, has sparked significant debate with his critical stance on the traditional processes of Ḥadīth collection and documentation. His arguments challenge long-standing views and practices, questioning the reliability of certain narrators and the methodologies employed in the early Islamic centuries. Aiming to contribute to the ongoing discourse surrounding the authenticity and methodology of Ḥadīth compilation within Islamic tradition, this paper provides a critical analysis of the views of Abū Rayyah on the recording of Ḥadīth, examining the historical context and scholarly responses to his critiques. Through a comprehensive review of primary sources, including Abū Rayyah's own writings and the responses from other Islamic scholars, the paper evaluates the strengths and weaknesses of his arguments. This involves analyzing his methodological approaches, his use of evidence, and the broader implications of his critiques for Islamic jurisprudence and theology. Ultimately, this study seeks to provide a balanced assessment of Abū Rayyah's contributions to the study of Ḥadīth, acknowledging his role in prompting critical reflection and debate while also considering the validity of the critiques against his views. By doing so, the paper aims to enhance the understanding of Ḥadīth recording practices and their impact on Islamic thought and practice.